Chronic pain in the elderly: Exploring cellular and molecular mechanisms and therapeutic perspectives - García-Domínguez, Mario (Frontiers in Aging, 2024)
Chronic pain is a debilitating condition frequently observed in the elderly, involving numerous pathological mechanisms within the nervous system. Diminished local blood flow, nerve degeneration, variations in fiber composition, alterations in ion channels and receptors, accompanied by the sustained activation of immune cells and release of pro-inflammatory cytokines, lead to overactivation of the peripheral nervous system. In the central nervous system, chronic pain is strongly associated with the activation of glial cells, which results in central sensitization and increased pain perception. Moreover, age-related alterations in neural plasticity and disruptions in pain inhibitory pathways can exacerbate chronic pain in older adults. Finally, the environmental influences on the development of chronic pain in the elderly must be considered. An understanding of these mechanisms is essential for developing novel treatments for chronic pain, which can significantly improve the quality of life for this vulnerable population.